Methodological Evolution and Convergence: A Comparative Study of Legal Istinbāṭ in the Fatwas of MUI, Nahdlatul Ulama, and Muhammadiyah - Asro Asro; Jaenudin Jaenudin (al-Afkar, Journal For Islamic Studies, 2023)
Islamic legal authority in Indonesia is distributed among three primary institutional pillars: the Indonesian Council of Ulama (MUI), Nahdlatul Ulama, and Muhammadiyah. This research investigates their methodological frameworks of legal istinbāṭ until 2022 to address the persistent gap between finite religious texts and the infinite complexity of modern contexts. Employing a qualitative-comparative method through library research, the study analyzes purely textual data from official institutional records and academic publications. The findings reveal that MUI utilizes a hierarchical approach (Nash Qath’i, Qauli, and Manhaji) designed to achieve national consensus through collective legal reasoning. Nahdlatul Ulama maintains traditionalist identity through its tiered Qauli, Ilhaqi, and Manhaji methods, emphasizing school-based continuity. Conversely, Muhammadiyah employs a reformist Manhaj Tarjih via Bayani, Ta’lili, and Istishlahi procedures to prioritize rational evidence. Divergent legal outcomes appear in sectors such as digital family law and cryptocurrency. The study concludes that despite divergent epistemological foundations, these institutions increasingly converge on Maqāṣid al-Sharī’ah as a primary normative compass. This evolution facilitates a balanced “Indonesianization” of Islamic law within a modern pluralistic landscape.